PARAMETRIC STUDY OF ROOF TOP SOLAR CHIMNEY - K.V., SREEJAYA (2013)
The Roof Top Solar Chimney is a solar thermal system which is mainly used for ventilation applications. The system performance is influenced by many designs and operating parameters. The current research work was directed to investigate the inl1uencing parameters on the system performance such as the inlet configuration, air inlet gap, the chimney height. chimney diameter. and the collector compm1ment design. The possibility of using the roof top solar chimney for small scale power generation was investigated.